Biochemical and hematological parameters in chronic kidney disease - Singh, S.; Bhatta, S. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Chronic kidney disease is a worldwide public health problem. It is associated with various biochemical and hematological abnormalities that leads to morbidity and mortality. The aim of this study was to evaluate the biochemical and hematological parameters in chronic kidney disease patients.Methods: This is a prospective cross sectional study conducted over a period of six months on 52 chronic kidney disease patients at Kist Medical College Teaching Hospital, Lalitpur, Nepal. Biochemical parameters such as urea, creatinine, calcium, phosphorous, sodium, potassium and hematological parameters like hemoglobin, hematocrit, red blood cell count, total leukocyte count, platelet count were measured using standard techniques in chronic kidney disease cases and the findings were compared with age and sex matched controls. Results were analyzed using SPSS 21 for Windows.Results: Hemoglobin, hematocrit, red blood cell count, total leukocyte count and platelet count were reduced and statistically significant in chronic kidney disease patients compared to controls(p